PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) TERHADAP KUALITAS ENTERPRISE RISK MANAGEMENT (ERM) DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN ENERGI DI BURSA EFEK INDONESIA TAHUN 2020–2024 - Muhammad Naiyiron Romdoni; Eni Wuryani (CV. Denasya Smart Publisher, 2026)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) Disclosure on the quality of Enterprise Risk Management (ERM) and to investigate the moderating role of firm size. The study was conducted on energy sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. A quantitative approach was employed using secondary data obtained from annual reports and sustainability reports. The sample was selected using a purposive sampling method, resulting in 96 observations that met the research criteria. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that Environmental Disclosure has no effect on Enterprise Risk Management (ERM) quality. Social Disclosure has a positive effect on Enterprise Risk Management (ERM) quality, whereas Governance Disclosure has no effect on Enterprise Risk Management (ERM) quality. The moderation test reveals that firm size strengthens the effect of social Disclosure on Enterprise Risk Management (ERM) quality, indicating its role as a quasimoderator. These findings suggest that the social dimension is the ESG component that contributes most significantly to strengthening risk management practices in energy sector companies. This study implies that companies should enhance the quality of Social Disclosure and integrate it into risk management systems to support long-term corporate sustainability.